2008
DOI: 10.1270/jsbbs.58.375
|View full text |Cite
|
Sign up to set email alerts
|

Marker enrichment and construction of haplotype-specific BAC contigs for the polyembryony genomic region in Citrus

Abstract: Polyembryony, in which zygotic and apomictic embryos develop concurrently in a seed, is widespread in Citrus. To obtain further genomic information about the previously characterized map position of the polyembryony locus, the relationship among linkage maps from 3 different hybrid populations was determined using common markers flanking the polyembryony locus. By mapping the polyembryony locus with cleaved amplified polymorphic sequence (CAPS) markers in a F180 × 'Harumi' population, the polyembryony locus wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Through a continuous effort of DNA marker landing and BAC walking with DNA sequencing of Satsuma BAC clones, Nakano with colleagues enriched CAPS or SNP markers surrounding the polyembryony locus. They evaluated haplotype structure by means of these markers and constructed haplotype-specific BAC contigs that cover the genomic region of the polyembryony locus (Nakano et al 2008a). Comparative mapping among five cross populations with the developed DNA markers flanking the polyembryony locus demonstrated similar lineage of these markers, and it suggested that a region flanking the polyembryony locus could be conserved among a wide variety of polyembryonic citrus plants.…”
Section: Fine Mapping Of a Locus Involved In Polyembryonymentioning
confidence: 99%
“…Through a continuous effort of DNA marker landing and BAC walking with DNA sequencing of Satsuma BAC clones, Nakano with colleagues enriched CAPS or SNP markers surrounding the polyembryony locus. They evaluated haplotype structure by means of these markers and constructed haplotype-specific BAC contigs that cover the genomic region of the polyembryony locus (Nakano et al 2008a). Comparative mapping among five cross populations with the developed DNA markers flanking the polyembryony locus demonstrated similar lineage of these markers, and it suggested that a region flanking the polyembryony locus could be conserved among a wide variety of polyembryonic citrus plants.…”
Section: Fine Mapping Of a Locus Involved In Polyembryonymentioning
confidence: 99%
“…It is conceivable that a single or a few genes are involved in the somatic embryogenesis and several molecular markers linked to a polyembryonic locus controlling embryonic type (mono/polyembryony) have been developed [ 11 , 17 , 29 ]. In our previous studies [ 29 , 30 ], a major polyembryonic locus was located on linkage group 1 of the mandarin standard genetic map (AGI map) [ 36 ] and scaffold 1 of the clementine mandarin ( C. clementina hort ex. Tanaka) genome sequence [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…In earlier reports, it has been proposed that NE is controlled by either a single, two, or multiple loci ( Iwamasa et al , 1967 ; García et al , 1999 ; Hong et al , 2001 a ). In later studies, molecular markers related to NE were identified ( Nakano et al , 2008 a , b ; Kepiro and Roose, 2010 ). The most recent report on genetics of citrus NE suggested that the candidate genomic region for the polyembryony locus is represented by an approximately 380-kb fragment ( Nakano et al , 2012 ).…”
Section: Introductionmentioning
confidence: 99%